Pemanfaatan Zeolit Alam Sebagai Katalis Pada Tahap Transesterifikasi Pembuatan Biodiesel Dari Sawit Off Grade - Sari ' Ulfayana; Syaiful ' Bahri; Zuchra ' Helwani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Indonesia has abundance reserves of natural zeolite and hasn’t been used to the fullest purpose. Zeolite has many advantages, such as environmental friendly and economical properties of molecular sieves that could potentially be developed as a catalyst in the production of biodiesel from palm off grade. This study aims to produce biodiesel from low quality raw materials and determine the effectiveness of the process by looking at the effect of process conditions such as reaction temperature, molar ratio and catalyst concentration on the yield of biodiesel. The process of making biodiesel is done with a two-stage reaction that is esterification and transesterification reactions because the raw materials had a hight free fatty acid levels. Processing of the data in this study conducted by response surface methodology (RSM) using Design Expert 8.0 program, which is experimental design determined by central composite design (CCD), which consists of three variables. The highest biodiesel obtained as much as 97.79%-wt under the conditions, 60°C reaction temperature, 8:1 molar ratio and 3%-wt catalyst concentration. Characteristics of biodiesel produced will be analyze, that is density, kinematic viscosity, acid number and flash point, accordance to Indonesian biodiesel standards. Process conditions that give real effect on the yield of biodiesel produced is the reaction temperature and catalyst concentration. Keywords : biodiesel, esterification, natural zeolite, palm off grade, transesterification.